Again to the school… (Journal of Parents and Teachers, 2014)
Beautiful reflection brought about by the first day of school, in which the center is filled with children, illusions, laughter and in which a new course begins, a new opportunity to continue growing.
Keywords: New course; reflection; first day of school.